"BRIKET CATTAPA" ALTERNATIF BRIKET BIOARANG TERBARUKAN BERBAHAN BUAH KETAPANG (TERMINALIA CATTAPA) YANG RAMAH LINGKUNGAN - Hidayah, Nurul; Astarinugrahini, Iin; Maklunah, Lulu (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
Abstract This study is conducted to find out how to make ketapang (Terminaliacattapa) fruit-based charcoal briquettes and to reveal the effectiveness testing of its quality. The briquettes called cattapa briquettes were made from the charcoal of the ketapang (Terminaliacattapa) with the material ratio of 3: 1. The briquettes were then shaped and pressed with a special tool and dried under the sun for about 2-5 hours. The quality of cattapa briquettes was tested in two stages, namely testing the water content testing and the fuel testing. The results of the analysis on the calculation of the levels of water reduction show that the cattapa briquettes has a water content reduction as much as 58.38%, while the results of the fuel testing show that cattapa briquettes are less effective and the quality is not good.